The two-stage location model for multi-construction period of material warehouses - Wenbin Zhang; Yuejun Jin (PLoS ONE, 2025)
This article proposes a two-stage location model to construct a unified construction plan for multi-construction period material warehouses in the distribution network. Initially, we propose a honeycomb grid partitioning method aimed at managing the time-scale of electric power material demand through effective grid administration. Subsequently, we develop an optimization model for the first stage, which identifies the threshold for the upper limit of material transportation time and establishes the construction objectives for material warehousing during each construction period. To address the challenge posed by the inconsistent locations of material warehouses across different construction periods, we formulate an optimization model for the second stage. Finally, based on the spatial distribution of power demand in Taizhou City’s distribution network, we devise a comprehensive construction plan for a material warehouse system that spans four construction periods. By adding nine material warehouse locations, we achieve a reduction of 57.14% in the maximum transportation time for electric power materials. The method proposed in this article provides a general solution for the long-term planning of persistent structures by converting long-term planning into construction goals across multiple stages.